Islet cell plasticity and regeneration() - Migliorini, Adriana (Elsevier, 2014)
Insulin-dependent diabetes is a complex multifactorial disorder characterized by loss or dysfunction of β-cells resulting in failure of metabolic control. Even though type 1 and 2 diabetes differ in their pathogenesis, restoring β-cell function is the overarching goal for improved therapy of both diseases. This could be achieved either by cell-replacement therapy or by triggering intrinsic regenerative mechanisms of the pancreas. For type 1 diabetes, a combination of β-cell replacement and immunosuppressive therapy could be a curative treatment, whereas for type 2 diabetes enhancing endogenous mechanisms of β-cell regeneration might optimize blood glucose control. This review will briefly summarize recent efforts to allow β-cell regeneration where the most promising approaches are currently (1) increasing β-cell self-replication or neogenesis from ductal progenitors and (2) conversion of α-cells into β-cells.